2013 International Conference on Virtual Rehabilitation (ICVR) 2013
DOI: 10.1109/icvr.2013.6662095
|View full text |Cite
|
Sign up to set email alerts
|

Using virtual reality to induce cross-axis adaptation of postural control: Implications for rehabilitation

Abstract: Adaptation of sensorimotor processes has been studied for over a century. However, rigorous experimental approaches require controlling as many variables as possible to study the phenomenon, which limits generalizability. Conversely testing adaptation in an unconstrained ecologically valid situation makes it difficult to identify what parameters affect this process. This study utilizes virtual environments (VE) to create complex, but controlled environments to test visual, vestibular, and sensorimotor adaptati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 42 publications
0
6
1
Order By: Relevance
“…This would also explain the lower impact of visual incongruences on balance and locomotor patterns while treadmill running, as shown in Experiment 2. Our results contradict previous studies on walking, which showed an influence of an artificial optical flow on postural stability [31][32][33][34] and on locomotor patterns. In particular, Pailhous et al [17] found that when walking overground, stride length decreases in presence of an artificial optical flow.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…This would also explain the lower impact of visual incongruences on balance and locomotor patterns while treadmill running, as shown in Experiment 2. Our results contradict previous studies on walking, which showed an influence of an artificial optical flow on postural stability [31][32][33][34] and on locomotor patterns. In particular, Pailhous et al [17] found that when walking overground, stride length decreases in presence of an artificial optical flow.…”
Section: Discussioncontrasting
confidence: 99%
“…In this experiment, we tested if treadmill running is influenced by the presence and the manipulation of an optical flow. Studies show that the manipulation of the optical flow has a destabilizing effect on postural stability [31][32][33][34], and a significant influence on locomotor patterns when walking [15,17,21,22]. The results regarding modifications of gait parameters and their variability as an effect of a virtual optical flow are contradicting, suggesting a great influence of the specific setup, the walking mode (i.e., fixed speed vs. self-paced treadmill) and the time to adapt to the new environment.…”
Section: Introductionmentioning
confidence: 99%
“…We were also interested in determining how VE immersion might affect other motor control processes such as head stabilization (Wright et al, 2013 ) and whole-body postural control (Wright, 2013 ). In one study, subjects were exposed to physical accelerations while viewing a directionally discordant visual scene.…”
Section: The Perception-action Link In Vementioning
confidence: 99%
“…In another study applying a similar experimental test protocol to investigate posture control, we paired visually-depicted translation in one direction with an orthogonally directed translation of the support surface. This cross-axis stimulation resulted in a postural response in standing humans that showed entrainment with both the visual and the support surface stimuli (Wright, 2013 ). These findings may not be unexpected, since studies pre-dating VR technology have shown that postural control can be entrained to a visual stimulus by simulating movement of the entire room, when the floor is kept stationary (Lishman and Lee, 1973 ).…”
Section: The Perception-action Link In Vementioning
confidence: 99%
See 1 more Smart Citation